BENTONITE SURFACE FUNCTIONALIZATION BY MERCAPTO GROUP FOR MERCURY ION AND VAPOR ADSORPTION - Adiwijaya Saputra, Calvin
Mercury is a heavy metal that can be found naturally in oil and natural gas. Mercury in natural gas exist in the form of elemental mercury, organic mercury, particulate mercury, and ionic mercury. Mercury in natural gas becomes a problem because it can cause damage in equipment, catalyst poisoning, and is harmful towards safety and health of workers. The common method used to remove mercury from natural gas is adsorption. Bentonite is a kind of montmorillonite clay minerals that can be used as an adsorbent for ionic mercury and mercury vapor. Surface functionalization of bentonite can increase the adsorption capacity of bentonite. The purpose of this research is to do a surface functionalization of bentonite with mercapto group to increase its ability to adsorb ionic mercury and mercury vapor. Surface functionalization of bentonite can be done by refluxing acid activated bentonite with 3- mercaptopropyl trimethoxysilane (MPTMS) and toluene solvent. Mercapto functionalized bentonite is characterized by FTIR, XRD, SEM-EDS, zeta potential, and BET to confirm the success of surface functionalization of bentonite. Mercapto functionalized bentonite synthesis gives an optimum number of products at the condition of 1 hour acid activation and the use of 30 mL MPTMS. FTIR spectrum of mercapto functionalized bentonite produce two peaks in 2933 cm-1 and 2559 cm-1 caused by the stretching vibration of CH2 aliphatic group and -SH group. XRD diffractogram shows no change of structure in bentonite after the surface functionalization process. The decrease of intensity in XRD diffractogram shows that the surface of bentonite has been covered by mercapto organic group. SEM- EDS characterization shows the surface of mercapto functionalized bentonite becomes more rough and thicker and the appearance of S atom peak which is absent in raw bentonite. Zeta potential and BET characterization shows an increase in zeta potential and the surface area of mercapto functionalized bentonite. Zeta potential shows an increase from -53.3 mV for raw bentonite to -23.3 mV, -27.6 mV, and -24.6 mV for bentonite functionalized with 7.5 mL, 15 mL, and 30 mL MPTMS respectively. Surface area of bentonite shows an increase from 76.352 m2/g for raw bentonite to 114.936 m2/g for mercapto functionalized bentonite. Literature study is done to determine the potential of mercapto functionalized bentonite to adsorb mercury ion and mercury vapor. Literature study was done by PCA method. Based from the result of characterization, it can be concluded that mercapto functionalized bentonite was successfully produced. Based on literature study, mercapto functionalized bentonite has a potential to adsorb mercury vapor at low temperature that is used within natural gas process.